Anesthesia Method in LT in our Clinic - Kilercik, H.; Sahin, T.; Basyigit, S.; Bektas, M.; Dogan, H.; Koroglu, A.; Cicek, M. (Lippincott Williams & Wilkins, 2017)
[Abstract Not Available]
Joint International Congress of ILTS, ELITA and LICAGE -- MAY 24-27, 2017 -- Prague, CZECH REPUBLIC